Effects of dry oxidation treatments on monolayer graphene. (9th June 2017) - Ryu, Gyeong Hee; Lee, Jongyeong; Kang, Dongwoo; Jo, Hye Jin; Shin, Hyeon Suk; Lee, Zonghoon
Abstract: Ultraviolet–ozone (UVO) and oxygen plasma are widely used to modify the surface of materials because these processes are facile and accessible. These dry oxidation treatments are also commonly applied to 2D graphene and are presumed to induce similar oxidation effects on the graphene surface. However, in this work, these treatments are revealed to induce the formation of different types of defects on the surface of graphene because the UVO treatment causes a chemical reaction, whereas the oxygen plasma treatment causes both physical and chemical reactions. The oxygen plasma treatment results mainly in topological defects, which effectively induce the attachment of oxygen atoms onto the treated surface; by contrast, the UVO treatment induces only the attachment of oxygen atoms onto the treated surface, without inducing lattice distortion. These results are confirmed mainly by atomic-resolution transmission electron microscopy imaging and electron energy loss spectroscopy. Using such facile dry oxidation treatments, we experimentally modified the surface states of graphene at the atomic scale.